1978
DOI: 10.4269/ajtmh.1978.27.751
|View full text |Cite
|
Sign up to set email alerts
|

The Antileishmanial Activity of Lepidines *

Abstract: A series of lepidines (6-methoxy-4-methyl-8-aminoquinoline derivatives) was studied in a hamster-Leishmania donovani model. Members of this class were found to have activity many-fold that of the standard, meglumine antimoniate (Glucantime). One of them, 8-(6-diethylamino-hexylamino)-6-methoxy-4-methylquinoline, designated WR 6026, when given orally was over 700 times as effective as the standard antimonial drug.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

1980
1980
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(32 citation statements)
references
References 0 publications
1
31
0
Order By: Relevance
“…Many aminoquinoline compounds, substituted at positions 8, 7, 6 and 4, have been synthesized at the Walter Reed Army Institute for Research and have previously been shown to be effective against cutaneous leishmaniasis and visceral leishmaniasis (11)(12)(13)15), malaria (5), and recently, against Pneumocystis carinii-caused pneumonia (2). An examination of the data obtained in the present study demonstrates that interesting biological activities also exist in the 2-substituted quinoline alkaloids.…”
Section: Discussionmentioning
confidence: 80%
“…Many aminoquinoline compounds, substituted at positions 8, 7, 6 and 4, have been synthesized at the Walter Reed Army Institute for Research and have previously been shown to be effective against cutaneous leishmaniasis and visceral leishmaniasis (11)(12)(13)15), malaria (5), and recently, against Pneumocystis carinii-caused pneumonia (2). An examination of the data obtained in the present study demonstrates that interesting biological activities also exist in the 2-substituted quinoline alkaloids.…”
Section: Discussionmentioning
confidence: 80%
“…Therefore, there is a great need for the development of effective and safe drugs for the treatment of leishmaniasis. A number of studies of chemotherapy of leishmaniasis have been carried out during the last two decades (4,11,14,15,17,19,25). These studies indicate that amphotericin B, liposomal amphotericin B, and paromomycin are more active than the antimonial agents for visceral leishmaniasis and pentamidine for cutaneous leishmaniasis and that allopurinol is being clinically tested in treatment of cutaneous leishmaniasis (15).…”
Section: Resultsmentioning
confidence: 99%
“…The lack of orally administered effective agents for VL prompted the clinical development of WR6026, a primaquine analog found to be highly active in animal testing. [1][2][3] The only previous phase 2 study of the efficacy of WR6026 was performed in Kenya. 4 In that study, 16 patients with VL underwent treatment with WR6026 at doses ranging from 0.75-1.0 mg/kg/day for 2 weeks (8 patients) or 1 mg/ kg/day for 4 weeks (8 patients).…”
Section: Introductionmentioning
confidence: 99%